Regulatory B cells promote graft-versus-host disease prevention and maintain graft-versus-leukemia activity following allogeneic bone marrow transplantation. (4th March 2017) - Hu, Yue; He, Gan-Lin; Zhao, Xiang-Yu; Zhao, Xiao-Su; Wang, Yu; Xu, Lan-Ping; Zhang, Xiao-Hui; Yu, Xue-Zhong; Liu, Kai-Yan; Chang, Ying-Jun; Huang, Xiao-Jun
ABSTRACT: Regulatory B cells (Bregs) are involved in the pathogenesis of graft-versus-host disease (GVHD). However, whether Bregs can alleviate acute GVHD without compromising graft-versus-leukemia (GVL) effects remains unclear. Here, we evaluated the role of Bregs in acute GVHD and GVL activity in both a mouse model and a clinical cohort study. In the acute GVHD mouse model, co-transplantation of Bregs prevents onset through inhibiting Th1 and Th17 differentiation and expanding regulatory T cells. In the GVL mouse model, Bregs contributed to the suppression of acute GVHD but had no adverse effect on GVL activity. In the clinical cohort study, a higher dose of Bregs in allografts was associated with a lower cumulative incidence of acute GVHD but not with increased risk of relapse. Our data demonstrate that Bregs can prevent acute GVHD and maintain GVL effects and suggest that Bregs have potential as a novel strategy for acute GVHD alleviation.